The role of authenticity, involvement and experience quality in heritage destinations - Abdullah Uslu; Nuria Recuero-Virto; Ramazan Eren; Maria Francisca Blasco-López (Tourism & Management Studies)
This research explores the impact of authenticity and involvement on destination image, aiming to comprehend visitor satisfaction, experience quality, re-patronage intentions, willingness to pay more, and word-of-mouth. Structural equation modelling was employed for analysis using data from 394 visitors to Side, Turkey. According to research findings, authenticity and involvement positively influence destination image. The findings demonstrate that developing re-patronage intentions, word-of-mouth recommendations, and willingness to pay more can be facilitated through experience quality and satisfaction. Also, it is proved that satisfaction is positively influenced by destination image. Moreover, authenticity and involvement positively influence destination image. According to research results, to increase willingness to pay, it is imperative to offer a high-quality cultural tourism experience, wherein tourists gain knowledge about the heritage destination and enjoy the experience while deeply engaging with the surroundings. Furthermore, public and private organisations should design visitor experiences that consider authenticity and involvement to enhance destination image and increase customer satisfaction.